Diagnosis and management after life threatening events in infants and young children who received cardiopulmonary resuscitation. Issue 6876 (20th February 1993) - Samuels, M P; Poets, C F; Noyes, J P; Hartmann, H; Hewertson, J; Southall, D P
Abstract : OBJECTIVE--To determine the mechanisms and thereby appropriate management for apparent life threatening events treated with cardiopulmonary resuscitation in infants and young children. DESIGN--Prospective clinical and physiological study. SETTING--Royal Brompton Hospital or in patients' homes, or both. SUBJECTS--157 Patients referred at median age 2.8 months (range 1 week to 96 months), 111 (71%) had recurrent events, 44 were born preterm, 19 were siblings of infants who had died suddenly and unexpectedly, and 18 were over 12 months old. INTERVENTIONS--Multichannel physiological recordings, including oxygenation, in hospital (n = 150) and at home (n = 61). Additional recordings with electroencephalogram, video, or other respiratory measures were used to confirm diagnoses. Management involved monitoring of oxygen at home, additional inspired oxygen, anticonvulsant treatment, or child protection procedures. MAIN OUTCOME MEASURES--Abnormalities on recordings compared to published normal data and their correlation with clinical events; sudden death. RESULTS--53 of 150 patients had abnormalities of oxygenation on hospital recordings, 28 of whom had an accompanying clinical event. Home recordings produced physiological data from 34 of 61 patients during subsequent clinical events. Final diagnoses were reached in 77 patients: deliberate suffocation by a parent (18), hypoxaemia induced by epileptic seizure (10), fabricated history and data (Munchausen syndrome by proxy; seven), acute hypoxaemia of probable respiratory origin (40), and changes in peripheral perfusion and skin colour without hypoxaemia (two). Four patients died: three suddenly and unexpectedly (none on home oxygen monitors) and one from pneumonia. CONCLUSIONS: Identification of mechanisms is essential to the appropriate management of infants with apparent life threatening events.